Cardiovascular and upper gastrointestinal bleeding consequences of low-dose acetylsalicylic acid discontinuation - Soriano, Lucía Cea; Bueno, Héctor; Lanas, Angel; Rodríguez, Luis A. García (Thrombosis and Haemostasis, 2013)
It was the aim of this study to investigate whether low-dose acetylsalicylic acid (ASA) therapy for secondary cardiovascular prevention should continue, despite the risk of gastrointestinal bleeding. We aimed to make a clinically meaningful benefit–risk assessment regarding the cardiovascular and gastrointestinal consequences of ASA discontinuation. This case–control study used The Health Improvement Network UK primary care database to identify patients aged 50–84 years during 2000–2007 with a first ASA prescription for secondary cardiovascular prevention (N = 39,513). New cases of non-fatal myocardial infarction (MI)/coronary death (n = 1,222), ischaemic stroke (IS)/transient ischaemic attack (TIA) (n = 673) and upper gastrointestinal bleeding (UGIB) (n = 169) were identified after a mean follow-up of 3.2, 3.4 and 4.0 years, respectively. ASA discontinuers before the index date were identified. Attributable risks associated with ASA discontinuation were calculated and National Institute for Health and Clinical Excellence annual economic data were used to estimate healthcare costs. The cumulative incidences of non-fatal MI/coronary death, IS/TIA and UGIB among ASA discontinuers within the first year of follow-up were 17, 11 and 1.6 per 1,000 persons, respectively. This corresponds to eight extra cardiovascular events, and a reduction of 0.4 UGIB events per year compared with current ASA users. Extrapolating to the UK population aged over 50 years, avoiding discontinuation of ASA could prevent 12,786 coronary and 7,672 cerebrovascular events/year, at the expense of 1023 extra UGIB events, saving approximately £100 million/year. In conclusion, preventing patients with cardiovascular disease from discontinuing ASA could result in substantial clinical and economic gains.
Keywords: Aspirin; medication adherence; Primary Health Care; cardiovascular; gastrointestinal haemorrhage